Digital elevation models constructed from JARE aerial photographs ... - Hata, Shuntaro; Kawamata, Moto; Doi, Koichiro (Arctic Data archive System (ADS), Japan, 2023)
This is a dataset for the digital elevation models constructed from aerial photographs of LKI(Lake Kaminotani-Ike; 69.495 degree S, 39.7579 degreeE). ...